Analisis Imbalan Faktor Produksi Usahatani Padi Sawah di Kabupaten Banjar - Rifiana Rifiana (AGRIDES: Jurnal Agribisnis Perdesaan, 2012)
The study aims are to analyze revenue, profitability and feasiability; to analyze the return for the production factors as well as knowing the problems faced by farmers in growing paddy. The study ws conducted in Kabupaten Banjar because this regency is one of rice production center in South Kalimantan. The respondents, were taken from 4 villages by using proportional random sampling. The results, by using the cost analysis, showed that the average income of paddy farmers was Rp. 6,649,249.84 per hectare, the average profit was Rp. 3,079,879.621 per hectare and RCR was 1.468 (per one unit of cost, make a profit of 46.8%). Although integrally paddy farming was profitable, but partially paddy farming in the study area was not economically advantageous, because the return for land, labor and capital were lower than its opportunity cost. Problems faced by paddy farmers were internal problem related to farm management, and external problems such as lack of price information and weaknesses in existing systems and institutions.